Phonon‐Related Monochromatic THz Radiation and its Magneto‐Modulation in 2D Ferromagnetic Cr2Ge2Te6. Issue 1 (29th October 2021) - Cheng, Long; Li, Huiping; Lin, Gaoting; Yan, Jian; Zhang, Lei; Yang, Cheng; Tong, Wei; Ren, Zhuang; Zhu, Wang; Cong, Xin; Gao, Jingjing; Tan, Pingheng; et al.
Abstract: Searching multiple types of terahertz (THz) irradiation source is crucial for the THz technology. In addition to the conventional fermionic cases, bosonic quasi‐/particles also promise energy‐efficient THz wave emission. Here, by utilizing a 2D ferromagnetic Cr2 Ge2 Te6 crystal, first a phonon‐related magneto‐tunable monochromatic THz irradiation source is demonstrated. With a low‐photonic‐energy broadband THz pump, a strong THz irradiation with frequency ≈0.9 THz and bandwidth ≈0.25 THz can be generated and its conversion efficiency could even reach 2.1% at 160 K. Moreover, it is intriguing to find that such monochromatic THz irradiation can be efficiently modulated by external magnetic field below 160 K. According to both experimental and theoretical analyses, the emergent THz irradiation is identified as the emission from the phonon‐polariton and its temperature and magnetic field dependent behaviors confirm the large spin‐lattice coupling in this 2D ferromagnetic crystal. These observations provide a new route for the creation of tunable monochromatic THz source which may have great practical interests in future applications in photonic and spintronic devices. Abstract : To addressing the challenge of low radiation efficiency of current universal terahertz sources, a van der Waals ferromagnetic semiconductor‐based efficient monochromatic terahertz radiation is developed here. It takes advantage of the bosonic quasi‐particles, phonon‐polaritons, that be coupled by exciting terahertz photons and inherent inter‐layered phonons in Cr2 Ge2 Te6 . The radiation could also be effectively modulated by external magnetic fields.